The Tokugawa Bureaucracy and Urban Crises: A Revival of the Humanist Traditions of China and Japan in Ogyu Sorai's Political Writings - Satō, Yasuko (History compass, 2007)
Ogyu Sorai (1666-1728) is a Japanese Confucian scholar who formulated his political philosophy, honoring the benevolent Way of the ancient Chinese Sages. It was his firm conviction that the task of government is to bring peace to the people. This humanistic concern was indeed central to classical Confucianism before the rise of a bureaucratic empire like the Qin (221-206 bce). How then is it possible to account for this lofty idealization of early Chinese Confucianism and its relevance to Tokugawa Japan (1600-1868)? This paper explores how Sorai's pursuit of Chinese antiquity was pitted against Tokvgawa bureaucratic control in the Edo metropolis and how he celebrated the centrality of great human beings to the promotion of popular welfare. In this view, the institution of soceity rests ultimately on political personalities who govern the land virtuously, and not on enforcement of order by punishments. It is worth noting, however, that Sorai did not articulate this humanist position merely as a Sinologist. In his mind, the Confucian values of humane rulership and interpersonal and social ethics were conflated with the samurai ideals prior to the establishment of the centralized Tokugawa power structure. He was well acquainted with the mental prowess of Japan's military lords and with their commitment to the primacy of human potentialities in both the military and civil arts. Theoretically, the ideal drawn from the way of antiquity is decentralized rule, as samurai rulers were originally lords of their fiefs. The construction of a human order in autonomous regions is what Sorai considered to be essential to realizing a society where the people can enjoy peace and tranquility.